Modifiable risk factors to reduce renal cell carcinoma incidence: Insight from the PLCO trial - Gelfond, Jonathan; Al-Bayati, Osamah; Kabra, Aashish; Iffrig, Kevan; Kaushik, Dharam; Liss, Michael A. (Urologic oncology, 2018)
Identify modifiable factors contributing to renal cell carcinoma in the PCLO to target disease prevention and reduce health care costs. The prostate, lung, colorectal, and ovarian database were queried for the primary outcome of kidney cancer. Demographics were investigated, specifically focusing on modifiable risk factors. Statistical analysis includes the Student t-test for continuous variables, chi-squared or Fisher’s exact tests for dichotomous and categorical variables for bivariate analysis. The Cox proportional hazards model was used in a multivariate time-to-event analysis. We investigate existing data relating specifically to renal cancer. After missing data were excluded, we analyzed 149,683 subjects enrolled in the prostate, lung, colorectal, and ovarian trial and noted 0.5% (n = 748) subjects developed renal cancer. Age, male gender, body mass index, diabetes, and hypertension were all significant associated with renal cancer in bivariate analysis (P<0.05). Men have a significant increased risk of kidney cancer over women (hazard ratio [HR] = 1.85; 95% CI: 1.58–2.16; P<0.0001). Nonmodifiable risk factors that are associated with kidney cancer include age (HR = 1.05; 95% CI: 1.01; 1.05, P = 0.001). Modifiable risk factors include obesity measured by body mass index (HR = 1.05; 95% CI: 1.02–1.07; P<0.0001), hypertension (HR = 1.32; 95% CI: 1.13–1.54; P = 0.0004), and smoking in pack-years (HR = 1.04; 95% CI: 1.02–1.07; P = 0.0002). Obesity, hypertension, and smoking are the 3 modifiable risk factors that could aggressively be targeted to reduce renal cell carcinoma. •Lifestyle modifications can impact kidney cancer incidence and outcomes.•Modifying lifestyle factors could be utilized in prevention of kidney cancer in high-risk patients.•Obesity, hypertension ion, and smoking could be aggressively targeted to reduce renal cell cancer.